Determination of Internet Banking Customer Satisfaction - Study at SOE Bank in Indonesia - Murdifin, Imaduddin; Nasir, Munawir; Ashoer, Muhammad; Syahnur, Muh. Haerdiansyah (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2021)
This study seeks to identify the role of perception of information technology, service quality, and trust on customer satisfaction of internet banking users in several State-Owned Enterprises (SOE) Banks in Indonesia. The study involved 228 respondents from BBRI, BMRI, and BBNI. The stages in data analysis involve the classical assumption, validity & reliability, and effect test using PLS-SEM. The results accept all hypotheses with positive and significant effects. This study finds that the optimal use and application of information technology systems can increase perceptions of internet banking use on customer satisfaction at SOE banks in Indonesia.